In vitro effect of hCG on cryptorchid patients’ gubernacular cells: a predictive model for adjuvant personalized therapy - Andrea Errico; Giulia Ambrosini; Sara Vinco; Emanuela Bottani; Elisa Dalla Pozza; Nunzio Marroncelli; Jessica Brandi; Daniela Cecconi; Ilaria Decimo; Filippo Migliorini; Nicola Zampieri; Ilaria Dando (Cell Communication and Signaling)
Abstract Background Cryptorchidism is the absence of one or both testicles in the scrotum at birth, being a risk factor for testis cancer and infertility. The most effective method to treat cryptorchidism is orchiopexy, followed by human chorionic gonadotropin (hCG) therapy; however, a portion of treated patients do not show a significant improvement in testis volume and vascularization after adjuvant therapy. Methods In this study, we generated an in vitro model to predict the patient response to hCG by cultivating and treating primary cells derived from five cryptorchid patients’ biopsies of gubernaculum testis, the ligament that connects the testicle to the scrotum. On these in vitro cultured cells, we analyzed the effect of hCG on cell proliferation, tubular structure formation, cellular respiration, reactive oxygen species content, and proteome. Results We demonstrate that in vitro hCG stimulates gubernacular cells to proliferate and form vessel-like structures to a different extent among the five cryptorchid patients’ cells, with a decrease in oxygen consumption and reactive oxygen species generation. Furthermore, from the proteomic analysis, we show that hCG regulates the intra- and extra-cellular organization of gubernacular cells together with a massive regulation of the antioxidant response. Conclusions Hereby, we characterized the cellular and molecular effects of hCG, demonstrating that the diverse patient response to hCG may be ascribable to their age since young patients better respond in vitro to the hormone, supporting a prompt surgical procedure and subsequent therapy. Trial registration The study was conducted in accordance with the Declaration of Helsinki and approved by the Institutional Ethics Committee of “Azienda Ospedaliera Universitaria Integrata” (AOUI) of Verona, Italy (“ANDRO-PRO”, protocol code N. 4206 CESC of 26 April 2023).